Field‐Effect Transistors: All Solution‐Processed, Hybrid Light Emitting Field‐Effect Transistors (Adv. Mater. 37/2014). (October 2014) - Muhieddine, Khalid; Ullah, Mujeeb; Pal, Bhola N.; Burn, Paul; Namdas, Ebinazar B.
<x xml:space="preserve">Abstract</x> M. Ullah, E. B. Namdas, and co‐workers present on page 6410 the first all‐solution‐processed hybrid light‐emitting transistors, and demonstrate the effectiveness of their operation with three organic emissive materials. This approach involves the fabrication of a bilayer device structure using a solution of organic emissive material, and a sol–gel of zinc tin oxide. The use of nonplanar contacts is also demonstrated in this study as playing a crucial role in the enhanced optoelectronics characteristics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>